2009
DOI: 10.1002/etc.48
|View full text |Cite
|
Sign up to set email alerts
|

Pulp and paper mill effluents induce distinct gene expression changes linked to androgenic and estrogenic responses in the fathead minnow (Pimephales promelas)

Abstract: Although effluent treatment systems within pulp and paper mills remove many toxicants and improve wastewater quality, there is a need to understand and quantify the effectiveness of the treatment process. At a combined news and kraft pulp and paper mill in northwestern Ontario, Canada, fathead minnow (FHM) reproduction and physiology were examined before, during, and after a short-term (6-d) exposure to 10% (v/v) untreated kraft mill effluent (UTK), 25% (v/v) secondary treated kraft mill effluent (TK), and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
(94 reference statements)
0
20
0
Order By: Relevance
“…Furthermore, effluent from sewage treatment plants on the Yeongsan and Seomjin Rivers has been shown to contain OP at a level as high as 0.5 ng/L (2.42 nM) (Duong et al, 2010). Another study found that ER␣ and VTG transcription was induced by exposure to paper mill outfall in male fathead minnow (Pimephales promelas) (Werner et al, 2010). Moreover, increased plasma VTG levels have been reported in male R. catesbeiana in Korea (NIER, 2003).…”
Section: Environmental Concernsmentioning
confidence: 94%
“…Furthermore, effluent from sewage treatment plants on the Yeongsan and Seomjin Rivers has been shown to contain OP at a level as high as 0.5 ng/L (2.42 nM) (Duong et al, 2010). Another study found that ER␣ and VTG transcription was induced by exposure to paper mill outfall in male fathead minnow (Pimephales promelas) (Werner et al, 2010). Moreover, increased plasma VTG levels have been reported in male R. catesbeiana in Korea (NIER, 2003).…”
Section: Environmental Concernsmentioning
confidence: 94%
“…Similarly, other studies noted the occurrence of masculinization in fish that were downstream of bleached kraft pulp and paper effluent point sources. This effect was due to the interaction of androgen-like compounds with the androgen receptor AR (Parks et al 2001;Larsson et al 2006;Wartman et al 2009;Werner et al 2010). In laboratory studies, the agonist and/or antagonist effects of many chemicals have been tested using either in vitro, in vivo, or both types of assay (Table 1).…”
Section: Estrogen-and Androgen-like Endocrine Disrupting Contaminantsmentioning
confidence: 99%
“…Werner et al 2010). In our studies, sediments from sites 1 km and 3 km downstream of the mill failed to induce cyp1a in juvenile zebrafish, when compared to the upstream reference site (RN).…”
Section: Industrial Sediment Ppm: Responses Of Estrogenic Biomarkersmentioning
confidence: 51%